รูปภาษาแทนสิ่งอ้างถึงในบทสนทนาของเด็ก - รติธรรมกุล, ธีราภรณ์ (วารสารอักษรศาสตร์, 2016)
บทความวิชาการนี้มีวัตถุประสงค์ที่จะนำเสนองานวิจัยต่างๆ ที่เกี่ยวกับการเลือกใช้รูปภาษาแทนสิ่งอ้างถึงในบทสนทนาของเด็ก โดยจะกล่าวถึงปัจจัยที่มีผลต่อการใช้รูปแทนสิ่งอ้างถึงอันได้แก่ สถานะของข้อมูลในปริจเฉท บทบาททางไวยากรณ์ในโครงสร้าง และข้อมูลรับเข้าที่เด็กได้รับ จากการศึกษาที่ผ่านมาพบว่าเด็กอายุประมาณ 2 ถึง 3 ปีจะมีพัฒนาการด้านทักษะทางวัจนปฏิบัติศาสตร์ซึ่งสำคัญในการใช้รูปแทนสิ่งอ้างถึงและสามารถเรียนรู้ที่จะใช้รูปแทนสิ่งอ้างถึงตามลักษณะเฉพาะของภาษาที่ได้รับ Referential forms in children's conversations Theeraporn Ratitamkul This review article aims to present an overview of research on referential choice in child conversation. Factors affecting children’s use of referential forms will be discussed, namely, the status of referents in discourse, the grammatical roles of referents in clauses and the input to which children are exposed. Previous studies have shown that children aged two to three years old are developing pragmatic skills which are important in selecting appropriate referential forms. Children at this age are also learning to use referential forms according to the norms of their languages.